Back Cover: Reversible Hydrogen Uptake/Release over a Sodium Phenoxide–Cyclohexanolate Pair (Angew. Chem. Int. Ed. 10/2019). Issue 10 (14th February 2019) - Yu, Yang; He, Teng; Wu, Anan; Pei, Qijun; Karkamkar, Abhijeet; Autrey, Tom; Chen, Ping
Abstract : Hydrogen uptake and release in arene–cycloalkane pairs is an attractive strategy for hydrogen storage but is hampered by the large enthalpy change associated with dehydrogenation. In their Communication onpage 3102 ff., P. Chen, T. He, A. Wu, and co‐workers describe how reversible hydrogen storage under moderate conditions is possible with a sodiated phenoxide–cyclohexanolate pair.